The Role of Village Government in Optimizing Child Marriage Prevention in Pendua Village - Agustina, Lela; Abdurrahman, Abdurrahman; Agustin, Repalia; Riswan, Riswan; Hamdani, Muh (The Future of Education Journal, 2026)
Early marriage refers to a marital union involving individuals under the age of 16 for females and under 19 for males. In Pendua Village, North Lombok Regency, early marriage frequently occurs, prompting the village government to take measures to minimize the number of child marriages. This program aims to prevent child marriage in Pendua Village, North Lombok Regency. Several factors contribute to the occurrence of child marriage in Pendua Village, including both internal and external factors. Internal factors include personal desire, while external factors involve parents’ economic conditions, educational background, and environmental influences. The community’s perception of child marriage in Pendua Village tends to be positive, as the practice is considered customary and socially accepted.  The role of the government significantly influences community welfare. The Pendua Village government expresses concern that children below the legal age choose early marriage, as they should instead receive proper education and pursue higher levels of schooling. Consequently, the village government collaborates with traditional leaders and the local women’s school to address and minimize child marriage by conducting awareness campaigns in each hamlet, providing guidance through traditional leaders and hamlet heads, encouraging parents to motivate their children to continue their education, and strengthening the enforcement of marriage laws along with their sanctions.